Percepção de serviços ecossistêmicos por agricultores familiares em transição agroecológica e sua contribuição para a conservação - Kadry, Vívian Oliveira (Universidade Federal de São Carlos, 2017)
Knowing the perception of ecosystem services is a tool in establishing actions for the conservation of ecosystems. Especially in areas covered by the Atlantic Forest such as Ubatuba-SP, where communities use these services generated by nature. This study evaluated the perception of ecosystem services of 20 farmers that are in transition to ecologically-based farming practices in Ubatuba. Semi-structured interviews were used to identify witch services were perceived by the farmers. The responses were classified according to the functions of regulation, habitat, production and information. Then was calculated the Ecosystem Perception Consolidation Index (ICPE). In general there was low perception of the ecosystem services, and regulation and information functions got higher ICPE. There was dissociation of the relation between forest and agricultural production, because the services generated by the habitat function were perceived only by 30% of the farmers. The results showed the need to incorporate an integrated technical assistance linking extension and conservation agencies. Therefore, rescuing cultural values alongside modern technologies, farmers can contribute more significantly to the conservation of the local Atlantic Forest.
Perception of ecosystem services of family farmers in agroecological transition and their contribution to conservation
Keywords: Agricultura de base ecológica; Agricultura familiar; Comunidades tradicionais; Floresta Atlântica; Atlantic Forest; Ecologically-based agriculture; Family farming; Indigenous people; CIENCIAS AGRARIAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES